Health consequences of domestic violence against women in Serbia - Mijatović-Jovanović Vesna; Čanković Sonja; Milijašević Dragana; Ukropina Snežana; Jovanović Mladen; Čanković Dušan (Vojnosanitetski Pregled)
Background/Aim. Domestic violence against women is a significant public health problem resulting in serious health and social consequences, for women and their families. The aim of this study was to analyze the sociodemographic characteristic of women who were exposed to domestic violence, as well as the impact of violence on women's health. Methods. Data from cross-sectional study from the 2013 National Health Survey in Serbia were used analyzing 6,320 women aged 20–75 years. Univariate and multivariate logistic regression analyses were implemented to assess the association of exposure to domestic violence against women with sociodemographic characteristics, as well as with selected health indicators and health risk behaviors. Results. Out of total number of examined women, 307 (4.9%) reported that they experienced physical and/or psychological violence in the last 12 months. Divorced or separated women, poor women and women with poor social support had greater odds for exposure to domestic violence. Women who had experienced domestic violence were less likely to perceived their health as good than women who had not experienced domestic violence [adjusted odds ratio (AOR) = 0.47; 95% confidence interval (CI) = 0.32–0.71], and more likely to report severe or very severe pain (AOR = 2.41; 95% CI = 1.74–3.33), stress and pressure exposure (AOR = 2.62; 95% CI = 1.89–3.64) and depression (AOR = 3.24; 95% CI = 2.08–5.03). Exposure to violence was also associated with the use of sleeping pills or sedative (AOR = 2.21; 95% CI = 1.67–2.93), with frequent use of alcohol (AOR = 1.42; 95% CI = 1.08–1.86) and abortion (AOR = 3.11; 95% CI = 1.48–6.54). Conclusion. Women, victims of domestic violence are more likely to have physical and mental disorders compared to women who are not victims of domestic violence. Violence prevention demands a multisectoral approach, in which the health sector has a central role that includes early identification and recognition of abuse, appropriate care as well as documenting and reporting violence.